2006
DOI: 10.1089/cpb.2006.9.82
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Telepresence Levels on Internet Advertising Effects

Abstract: This study examined the dimensions of interactivity and vividness to propose three telepresence levels: content presence, social presence, and personal presence. Then, an experiment investigated the impact of different telepresence levels on Internet advertising. The effects of interactions between vividness of visual imagery (VVI) and product types in relation to telepresence levels and advertising effects were also analyzed. The study employed a factorial design: 4 (levels of telepresence) x 2 (product types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 17 publications
1
47
1
Order By: Relevance
“…They were firstly asked to browse the assigned mock website for five minutes. Although this study does not purport to examine the effect of website characteristics on perceived presence, two mock websites (i.e., high and low presence-inducing websites), which were developed by manipulating presence-inducing levels (Hopkins et al, 2004;Keng & Lin, 2006;Klein, 2003), were incorporated to create a variation in participants' perception of presence.…”
Section: Data Collection and Samplementioning
confidence: 99%
“…They were firstly asked to browse the assigned mock website for five minutes. Although this study does not purport to examine the effect of website characteristics on perceived presence, two mock websites (i.e., high and low presence-inducing websites), which were developed by manipulating presence-inducing levels (Hopkins et al, 2004;Keng & Lin, 2006;Klein, 2003), were incorporated to create a variation in participants' perception of presence.…”
Section: Data Collection and Samplementioning
confidence: 99%
“…Until now, many useful and valuable insights have been offered about the antecedents of telepresence in virtual environments (for a review, see for example Lee, 2004b), its variety of forms (e.g. Keng and Lin, 2006;Lombard and Ditton, 1997;Shen and Khalifa, 2008), as well as its consequences in the formation of enjoyment feelings and the state of flow (e.g. Novak et al, 2000;Nah et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These include analyses about the influence of the individual's ability to engage in mental imagery in their sense of telepresence (e.g. Keng and Lin, 2006;Sas and O'Hare, 2003;Thornson et al, 2009;Weibel et al, 2011). Others (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Telepresence is considered an important construct in virtual reality research where two main perspectives dominate: a psychological and a technological (Yin, Cicchirillo, & Drumwright, 2012). Various studies have found that presence influences the perceived product knowledge, brand attributes (Grigorovici & Constantin, 2004;Hopkins, Raymond, & Mitra, 2004), recall and recognition (Keng & Lin, 2006), attitudes towards advertisements (Hopkins et al, 2004) and purchase intentions. Generating a sense of presence depends on the media involved, user characteristics (perceptions of interactivity and vividness) and individual attention to media stimuli (Lessiter, Freeman, Keogh, & Davidoff, 2001).…”
Section: Virtual Reality -The Conceptmentioning
confidence: 99%